2012
DOI: 10.1021/am2018628
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Nanoparticles as a Support for Pt and PtRu Catalysts for Direct Methanol Fuel Cells

Abstract: Diamond in nanoparticle form is a promising material that can be used as a robust and chemically stable catalyst support in fuel cells. It has been studied and characterized physically and electrochemically, in its thin film and powder forms, as reported in the literature. In the present work, the electrochemical properties of undoped and boron-doped diamond nanoparticle electrodes, fabricated using the ink-paste method, were investigated. Methanol oxidation experiments were carried out in both half-cell and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 45 publications
1
51
0
1
Order By: Relevance
“…Different kinds of diamond nanoparticles (e.g., surface graphitized diamond nanoparticles with a diamond core covered by a graphitic carbon shell, bucky diamond nanoparticles with a nanoscale diamond core surrounded by a fullerene shell, and graphene coated diamond nanoparticles) have been used as the support to load catalysts (e.g., Pt [87][88][89][90][91][92][93], Ni [94,95], Ti [96], Pd [97], Pt/Ni [98], Pt/Ru [99][100][101][102], Sn/Pb [103], Pt/Eu [91,99], and metal oxides [104][105][106]). The mostly investigated electrocatalytic reactions include electrocatalytic oxidation of methanol/formic acid/CO as well as oxygen reduction reaction.…”
Section: Electrocatalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…Different kinds of diamond nanoparticles (e.g., surface graphitized diamond nanoparticles with a diamond core covered by a graphitic carbon shell, bucky diamond nanoparticles with a nanoscale diamond core surrounded by a fullerene shell, and graphene coated diamond nanoparticles) have been used as the support to load catalysts (e.g., Pt [87][88][89][90][91][92][93], Ni [94,95], Ti [96], Pd [97], Pt/Ni [98], Pt/Ru [99][100][101][102], Sn/Pb [103], Pt/Eu [91,99], and metal oxides [104][105][106]). The mostly investigated electrocatalytic reactions include electrocatalytic oxidation of methanol/formic acid/CO as well as oxygen reduction reaction.…”
Section: Electrocatalystsmentioning
confidence: 99%
“…The mostly investigated electrocatalytic reactions include electrocatalytic oxidation of methanol/formic acid/CO as well as oxygen reduction reaction. To load these catalysts on diamond nanoparticles, numerous approaches have been developed, including electrodeposition [88,92], chemical reduction [93], and microwaveassisted polyol synthesis [91,99]. For example, electrodeposition of Pt nanoparticles on un-doped diamond nanoparticles (5-100 nm in diameter) were conducted in 1.1 mM chloroplatinic acid solution.…”
Section: Electrocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The route used to prepare the suspensions (inks) of DNPs and BDDNPs for the electrochemical studies performed by La-Torre-Riveros and co-workers [63] shown to be well suitable to obtain useful electrochemical information on these nanoparticle diamond supported systems. The cyclic voltammetry results showed that there were significant differences between the undoped DNP and BDDNPs samples, with the latter exhibiting superior characteristics in terms of various electrochemical applications, including that of catalyst support.…”
Section: Recent Applications Of Bbd For Electrochemical Energy Storagmentioning
confidence: 99%